Influence of sintering additive on the electrical conductivity, chemical stability and sinterability of BaCe0.55Zr0.3Y0.15O3-δ - An, H.; Shin, D.W.; Choi, S.M.; Hong, J.; Yoon, K.J.; Son, J.-W.; Kim, B.-K.; Lee, J.-H. (Electrochemical Society Inc., 2015)
In this study, BaCe0.55Zr0.3Y0.15O3-δ was synthesized via solid state reaction (SSR) method and successfully sintered at relatively low temperature below 1400°C using various types of nickel oxide additives (simple oxide form, NiO and compound form, BaY2NiO5). In order to compare the effect of different forms of sintering additives, we investigated the electrical conductivity, chemical stability and sinterability via dilatometry, DC 4-probe conductivity measurement, XRD and TG analysis. In addition to the experimental results, possibility and limitation of compound form of sintering aid will also be addressed in this paper. ？ The Electrochemical Society.